Assessment of hepatoprotective and nephroprotective effects of Vitis vinifera leaf extract on carbon tetrachloride induced toxicity in rats - Kumar, Ashok; Pragi; Sharma, Amit; Kumar, Varun (Journal of Applied Pharmaceutical Research, 2024)
Background: Vitis vinifera is known for its antimicrobial activity; however, the hepatoprotective activity of aqueous extracts of aerial parts has also been reported, but the nephroprotective and hepatoprotective activity of ethanolic extracts have not yet been evaluated. Objective: To evaluate Vitis vinifera's hepatoprotective and nephroprotective activities against CCl4-induced toxicity in rats. Methods: Two doses of ethanolic extract of Vitis vinifera (100 and 200 mg/kg/day) were evaluated and compared with silymarin 100 mg/kg. Biochemical blood parameters like aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), Gamma-glutamyltranspeptidase (GGT), bilirubin, urea, uric acid, total protein and creatinine, and histopathologic changes of liver and kidney were studied and evaluated. Results: Vitis vinifera reduced the elevated blood levels of ALT, AST, ALP, urea, and creatinine, with the ethanol extract to 200 mg/kg/day being more effective. The histopathologic evaluation suggested that Vitis vinifera decreased hepatic and renal necrosis induced by CCl4. The more significant dose resulted in reductions in AST, ALT, GGT, ALP, and bilirubin of 54, 27, 56, 36, and 17%, respectively. Ethanolic extract 200 mg/kg/day also shows a reduction in elevated levels of Creatinine, Urea, Uric Acid, and Total Protein by 61%, 58%, 29%, and 9%, respectively. Conclusion: Hepatoprotective and nephroprotective activities of ethanol extract of Vitis vinifera were demonstrated, with ethanol extract to 200 mg/kg/day being the most effective. This presents scientific evidence for using medicinal plants such as Vitis vinifera in managing liver and kidney disorders.